Genome-wide transcriptome modulation in rice transgenic lines expressing engineered mitogen activated protein kinase kinase 6 - Kumar, Kundan (Landes Bioscience, 2014)
Mitogen activated protein kinase kinase (MAPKK) is the central module of MAPK cascade and also point of signal integration and divergence. To investigate the regulatory role of OsMKK6, the regulon of genes controlled by OsMKK6 was constructed by microarray analysis between constitutively activated overexpressing transgenic lines and the wild type rice. Regulated genes were identified in overexpressed constitutively activated OsMKK6 and they were further subdivided on the basis of functional categories, viz. transcription, metabolism, signaling, defense and unknown function. These findings suggest the possible physiological role of OsMKK6 in modulating gene expression and signaling pathways during different stresses.